In vitro Antidiabetic and Antioxidant Potential of Annona reticulata L. Leaves - Kumari, Amulya; Patnaik, Amit; Sharan, Latika (Defence Life Science Journal, 2024)
Annona reticulata L. leaf decoction has ethnopharmacological relevance as it is administered orally with cow’s milk to treat diabetes in west Godavari district of Andhra Pradesh, India. The prime objective of the study was to evaluate the antidiabetic and antioxidant capacity of Annona reticulata L. leaf extract in various solvents. Ethanol, methanol, acetone, DMSO, and aqueous extract were prepared by cold extraction method. Antidiabetic and antioxidant activity was evaluated by invitro glucose uptake activity by yeast cells, alpha-amylase inhibition assay, alpha-glucosidase inhibition assay, DPPH free radical scavenging assay, and CUPRAC antioxidant activity. In the yeast glucose uptake assay, the glucose uptake % ranges from 57.52±0.11(15 mM glucose) to 71.74±0.11 (5 mM glucose). The glucose uptake percent increased with increasing extract concentration (1-5 mg/ml), whereas it decreased with increasing glucose concentration (5 mM, 10 mM, and 15 mM). The ethanol extract demonstrated the highest α-amylase inhibitory activity, as indicated by the IC50 value of 41.64±1.43 μg/ml, and methanol extract exhibited the highest α-glucosidase inhibitory activity with an IC50 value of 18.26±0.03 μg/ml. In the DPPH antioxidant assay, the acetone extract has displayed the highest level of free radical scavenging activity at 20 μg/ml (64.12%) with an IC50 value of 16.58±0.07 μg/ml. Annona reticulata L. leaf extract possesses significant antidiabetic and antioxidant characteristic as evidenced by in vitro antidiabetic assay, DPPH, and CUPRAC antioxidant assay. The results of the study support the ethnopharmacological use of the plant for the treatment of diabetes.